Acute and long‐term consequences of exposure to organophosphate nerve agents in humans. (29th August 2018) - Figueiredo, Taiza H.; Apland, James P.; Braga, Maria F. M.; Marini, Ann M.
Summary: Nerve agents are organophosphate (OP) compounds and among the most powerful poisons known to man. A terrorist attack on civilian or military populations causing mass casualties is a real threat. The OP nerve agents include soman, sarin, cyclosarin, tabun, and VX. The major mechanism of acute toxicity is the irreversible inhibition of acetylcholinesterase. Acetylcholinesterase inhibition results in the accumulation of excessive acetylcholine levels in synapses, leading to progression of toxic signs including hypersecretions, tremors, status epilepticus, respiratory distress, and death. Miosis and rhinorrhea are the most common clinical findings in those individuals acutely exposed to OP nerve agents. Prolonged seizures are responsible for the neuropathology. The brain region that shows the most severe damage is the amygdala, followed by the piriform cortex, hippocampus, cortex, thalamus, and caudate/putamen. Current medical countermeasures are only modestly effective in attenuating the seizures and neuropathology. Anticonvulsants such as benzodiazepines decrease seizure activity and improve outcome, but their efficacy depends upon the administration time after exposure to the nerve agent. Administration of benzodiazepines may increase the risk for seizure recurrence. Recent studies document long‐term neurologic and behavior deficits, and technological advances demonstrate structural brain changes on magnetic resonance imaging.